2007
DOI: 10.4028/www.scientific.net/msf.558-559.301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Changing Homogenization Treatment on the Particle Structure in Mn-Containing Aluminium Alloys

Abstract: During casting and homogenisation of aluminium the microstructural fundament for further processing is made. Particle structure (dispersoids and primary particles), grain structure and level of elements in solid solution govern the mechanical and annealing properties of the material. In 3xxx-alloys, Mn in solid solution and Mn-containing dispersoids formed during homogenisation play an important role in controlling the recrystallization behaviour of the material [e.g. 1, 2, 3]. Other elements, such as Si, will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Here, the dispersoid density was higher for lower heating rates. This expectation was based on earlier studies, which showed an increase in dispersoid number densities with decreasing homogenization temperatures [10,22]. Such a relation suggests that the amount of time spent at lower temperatures could lead to an increase in number density.…”
Section: Density and % Areamentioning
confidence: 80%
See 1 more Smart Citation
“…Here, the dispersoid density was higher for lower heating rates. This expectation was based on earlier studies, which showed an increase in dispersoid number densities with decreasing homogenization temperatures [10,22]. Such a relation suggests that the amount of time spent at lower temperatures could lead to an increase in number density.…”
Section: Density and % Areamentioning
confidence: 80%
“…This may cause the results to vary greatly with the operator on duty. Such evaluations of dispersoid distributions may, for example, be done by measuring the width of the dispersoid-free zones (DFZs) [9], or measuring the change in density from the grain boundary towards the center of the grain [10]. These methods are time consuming and may be inaccurate and inadequate.…”
Section: Existing Methods For Assessing Spatial Uniformitymentioning
confidence: 99%
“…The string-like distribution is probably due to heterogeneous precipitation on dislocations, which was also observed in ref. [6]. The TEM and SEM images (Figures 2 and 3) show that the distribution of dispersoids in the rolled sample is homogeneous due to the high-density dislocations and sub-boundaries.…”
Section: Precipitation Kineticsmentioning
confidence: 93%
“…However, the dispersoids precipitated during the heat treatment of as-cast Al-Mn are heterogeneously distributed due to micro-segregation in the as-cast structure. It has been observed that the number density of dispersoids at the center of the dendrite arm was significantly lower than that in the periphery of the dendrite arm [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation